Gain Enhancement of Horn Antenna Using Meta Surface Lens - Manikandan, R.; Rao, P. H.; Jawahar, P. K. (Advanced Electromagnetics, 2018)
Three dimensional meta surface lens is proposed to improve the gain and beam shaping of horn antenna. Hence an array of SRR as a meta surface lens has been designed, fabricated and investigated. This meta surface lens can be used to convert the spherical wave to plane wave for a wide range of frequency. It is proved by permeability and permittivity of meta surface. In this work the operating bandwidth of the proposed antenna is in the range of 9GHz to 11GHz for satellite application. The radiation pattern of E and H plane is sharpened in this work. The antenna 3dB beam width, and front to back ratio were 9.2, 28dB at 10GHz. The radiation characteristics of horn antenna with meta surface have been studied numerically and confirmed experimentally, showing an average gain improvement of ~3dB with respect to horn antenna without meta surface lens.